الحق الدامغ - الخليلي, أحمد بن حمد (دار الحكمة, 2008)
Keywords: Polémique

شكر المنة في نصر السنة لأبي العباس أحمد بن محمد المكني : 1045 - 1122 هـ : دراسة وتحقيقا - الضاحي, عبد العزيز بن عبد الله (جامعة الإمام محمد بن سعود الإسلامية, 2000)
Keywords: Polémique

Muhali̇f Firak Kaynaklarinda İbâdi̇yye - Ateş, Orhan (Uluslararası Sosyal Bilimler Dergisi, 2017)
In this article, the subject of Ibadiyye in opposition sources will be discussed. The objections of the ibadis have not been sufficiently taken into account by the dominant paradigm. Political powers use the basic dynamics of society in their own interests in order to legitimize the actions they engage in. This approach is an official history view. Opposing / opposing history takes place against official history. For this reason, in order to reach the correct results while evaluating the historical events, the official history as well as the oppositional history should be taken into consideration.
Keywords: Polémique

Ebû Mutî’ Mekhûl en-Nesefî’nin Kitâbu’r-Red alâ’l Bida’ ve Ehli’l-Ehvâ adlı eserinde İbâdiyye Değerlendirmesi - Ateş, Orhan (Uluslararası Sosyal Bilimler Dergisi, 2017)
Keywords: Polémique

جواب العزابة ردا على البهلولي على بن أبي الحسن - بن إسماعيل, أبي مهدي عيسى (سلسلة الفرائد والفوائد, 2016)
Keywords: Polémique

موقف الخوارج من المخالفين لهم و الرد عليهم - الغصن, سليمان بن صالح بن عبدالعزيز (مجلة الجامعة الإسلامية, 2006)
Keywords: Polémique

Al-Ḥiwār al-Ibāḍī al-Mālikī, Ta’līf al-ʿĀlimayni al-Jalīlayni Ṣūla al-Ghadāmisī wa-Abī ‘l-ʿAbbās Aḥm. b. Saʿīd al-Shammākhī - الشماخي, أحمد بن سعيد (وزارة التراث القومي والثقافة, 2006)
Keywords: Polémique

الحق الدامغ - الخليلي, أحمد بن حمد (مكتبة مسقط, 2012)
Keywords: Polémique

الحوار الاباضي المالكي - الغدامسي, صوله بن ابراهيم; الشماخي, أحمد بن سعيد (وزارة التراث والثقافة, 2014)
Keywords: Polémique

الحق الدامغ - الخليلي, أحمد بن حمد (الكلمة الطيبة, 2017)
Keywords: Polémique